A Benefits Prioritization Analysis on Adopting BIM Systems Against Major Challenges in Megaproject Delivery - Chen, Zhen; Agapiou, Andrew; Li, Heng (Frontiers in Built Environment, 2020)
Purpose: A recent research and development experiment on benefits analysis for adopting building information modelling/management (BIM) systems in megaproject delivery across work stages with regard to the needs of project stakeholders. It focuses on a new approach to benefits prioritisation to support decision making against major challenges in megaproject delivery. Methodology: The study was underpinned by an extensive literature review on relevant research and practices across the world, and a questionnaire-based survey on the benefits from adopting BIM in megaproject delivery in Australia. In addition, this study yields new tools for value analysis with regard to the adoption of BIM systems in megaproject delivery, and this include a new calculation method for benefits prioritisation, and a new value compass tool to support decisions making on BIM adoption. Findings: Through the extensive literature review that covers multidisciplinary areas relating to the use of BIM, a set of generic hypotheses was formulated on the comparative level of technical value that various stakeholder groups are expected to achieve from adopting BIM systems in megaproject delivery. These hypotheses were tested by using the questionnaire-based survey. A new benefits prioritisation approach was developed to identify the key benefits of BIM systems in megaproject delivery. In addition, a compass tool was also developed to visualise the status of value achievement across project stakeholders in dealing with major challenges in megaproject delivery. Implications: By using data collected from the Australian megaproject sector in addition to academic review, this study revealed current professional perceptions on the benefits of adopting BIM systems in megaproject delivery in comparison with data and information reported by professionals concerning the adoption of BIM systems from both generic and specific point of view across multiple megaproject stakeholders. Value: Useful information for both academic research and practical services in the context of quantitative Cost-Benefit Analysis on the adoption of BIM systems in megaproject delivery when major challenges on professional competence, budget, schedule and sustainability need to be seriously dealt with. Findings from this experimental study can inform value engineering practice at both strategic and tactic level with regard to adopting BIM systems in megaproject delivery.